Machine ethics: stato dell’arte e osservazioni critiche - Cracco, Leonardo (Filosofia, 2020)
This essay aims to introduce the field of study known as machine ethics, viz. the aspect of the ethics of artificial intelligence concerned with the moral behavior of AI systems. I discuss the present potential of this technology and put forward some ethical considerations about the benefits and perils deriving from the development of this field of research. There is an urge of debate, considering that there is an increase in machine usage in ethically-sensitive domains, to ensure that future technology becomes advantageous for humans and their well-being.